HUBUNGAN ANTARA HARGA DIRI DENGAN SUCCESSFUL AGING PADA LANSIA - Yoana Elvita Fetriana; Christiana Hari Soetjiningsih (Program Studi S1 Psikologi, 2019)
Basically, every elderly can achieve successful aging in his old age, depending on the number of factors influencing it, such as self-esteem factors. Successful aging will indirectly be influenced by these factors. Therefore, this research aims to find out if there is a relationship between self-esteem with successful aging in elderly. This type of research was taken using quantitative research methods with saturated sample models. The samples in this study amounted to 50 people aged 60-80 years. The results showed that the results of the correlation coefficient (r) =-0.064 with a Sig value of 0.329 p > 0.05. It can be concluded that there is no relationship between self-esteem and successful aging in elderly. Keywords: Self Esteem, successful aging, elderly